Knowledge production in the 21st century: Some thoughts - Le Grange, Lesley (South African Journal of Higher Education, 2016)
Knowledge production in the 21st century is changing rapidly as both universities and societies transform in a world that is increasingly interconnected in so many different ways. Challenges associated with these transformations include: globalisation, the compression of time and space, the ascendency of neoliberalism, a pendulum swing from basic to applied research, the emergence of transdisciplinary research, the internationalisation of indigenous knowledges, and complex societal issues (e.g. environmental destruction, poverty, unemployment, disease). This special issue of SAJHE focuses on how knowledge production has occurred in transnational and local spaces in view of these challenges.